2019
DOI: 10.3390/antiox8090343
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Chemical Characterization and Multidirectional Biological Investigation of Leaves and Bark Extracts of Anogeissus leiocarpus (DC.) Guill. & Perr. (Combretaceae)

Abstract: Anogeissus leiocarpus (DC.) Guill. & Perr. (Combretaceae) has a long history of use by folk populations for the management of multiple human ailments. Based on the published literature, there has been no attempt to conduct a comparative assessment of the biological activity and the phytochemical profiles of the leaves and stem bark of A. leiocarpus extracted using methanol, ethyl acetate, and water. By high-performance liquid chromatography with electrospray ionization mass spectrometric detection (HPLC-ESI-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…Moreover, in agreement with Orlando et al [ 26 ], we found that the extraction yields considerably varied between different plant parts, such that Soxhlet extraction with methanol resulted in a low extraction yield for the roots (10.8%) compared to the stem bark (47.1%) and leaves (50.8%) ( Figure 6 ). Thus, the total antimycobacterial activity for the root Soxhlet methanol extract was calculated to be 43.2 mL/g (108 mg extracted from 1 g plant material divided by the MIC in mg/mL, 2.5 mg/mL).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, in agreement with Orlando et al [ 26 ], we found that the extraction yields considerably varied between different plant parts, such that Soxhlet extraction with methanol resulted in a low extraction yield for the roots (10.8%) compared to the stem bark (47.1%) and leaves (50.8%) ( Figure 6 ). Thus, the total antimycobacterial activity for the root Soxhlet methanol extract was calculated to be 43.2 mL/g (108 mg extracted from 1 g plant material divided by the MIC in mg/mL, 2.5 mg/mL).…”
Section: Discussionsupporting
confidence: 91%
“…In our previous investigation, we tentatively characterized ten unknown ellagitannins in this stem bark ethyl acetate extract of A. leiocarpa based on HPLC-UV-DAD data (UV λ maxima and retention times) [ 18 ]. Moreover, previously reported ellagitannins in the stem bark and leaves of A. leiocarpa include a corilagin sanguiin H-4, punicalagin, castalagin (1-epi-vescalagin), casuarinin, chebulagic acid, and punicacortein ( Figure 7 ) [ 26 , 31 ]. These mentioned ellagitannins may play a significant role for the in vitro antimycobacterial effect of the stem bark ethyl acetate extract of A. leiocarpa that we present in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the cell viability tended to decrease under the biocompatibility limit (80%) at the highest formula concentration (1600 µg/mL). It is rational to hypothesize that the reduced cell viability at the highest tested concentration could be related to the paradoxical phenolic compound-induced oxidative stress that often occurs at elevated concentrations [45,46]. Conversely, under the limit of biocompatibility, the single extracts and Fluxonorm ® were able to contrast the burden of oxidative stress and inflammation in isolated rat prostate specimens challenged with LPS, an ex vivo model of prostatitis [11,47].…”
Section: Resultsmentioning
confidence: 99%
“…In the Soxhlet technique, the plant materials (5 g) were extracted with 100 mL methanol by using Soxhlet apparatus for 6 h. Extracts were obtained by using a vacuum evaporator. Water extracts were lyophilized, and all extracts stored in a refrigerator [18,19].…”
Section: Plant Materials and Preparation Of Extractsmentioning
confidence: 99%